Gustav Stresemann : Weimar's greatest statesman - Wright, Jonathan, 1941- (Oxford University Press, 2004)
Gustav Stresemann was the exceptional German political figure of his time. His early death in 1929 has long been viewed as the beginning of the end for the Weimar Republic and the opening through which Hitler was able to come to power. Stresemann's personality and talents as a politican held together the coalition that provided the only serious opposition to the Nazi party in the 1920s. On his death this opposition collapsed and along with it the only chance of establishing a stable. and democratic Germany at the heart of a stable Europe. - ;Gustav Stresemann was the exceptional political figu.